2003
DOI: 10.1016/s1074-5521(03)00169-8
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Inhibition of CD13/Aminopeptidase N by the Antiangiogenic Agent Curcumin

Abstract: CD13/aminopeptidase N (APN) is a membrane-bound, zinc-dependent metalloproteinase that plays a key role in tumor invasion and angiogenesis. Here, we show that curcumin, a phenolic natural product, binds to APN and irreversibly inhibits its activity. The direct interaction between curcumin with APN was confirmed both in vitro and in vivo by surface plasmon resonance analysis and an APN-specific antibody competition assay, respectively. Moreover, curcumin and other known APN inhibitors strongly inhibited APN-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(86 citation statements)
references
References 31 publications
7
78
0
1
Order By: Relevance
“…By directly binding small b-amyloid species, curcumin blocks aggregation and fibril formation in vitro and in vivo [51]. Curcumin irreversibly binds CD13/aminopeptidase N (APN) and inhibits tumor invasion and angiogenesis [55]. Curcumin has also been shown to inhibit the activity of lipoxygenase by binding lipoxygenase itself [65] or binding to phosphatidylcholine (PC) micelles and thereby inhibiting lipoxygenase 1 [74].…”
Section: Curcumin Interacts With Numerous Targetsmentioning
confidence: 99%
“…By directly binding small b-amyloid species, curcumin blocks aggregation and fibril formation in vitro and in vivo [51]. Curcumin irreversibly binds CD13/aminopeptidase N (APN) and inhibits tumor invasion and angiogenesis [55]. Curcumin has also been shown to inhibit the activity of lipoxygenase by binding lipoxygenase itself [65] or binding to phosphatidylcholine (PC) micelles and thereby inhibiting lipoxygenase 1 [74].…”
Section: Curcumin Interacts With Numerous Targetsmentioning
confidence: 99%
“…Pre-incubation with curcumin, an uncompetitive inhibitor, 34 was shown to block more than 85% of CD13 receptors (inset), leading to decreased b-gal expression in AdHNGR-infected Lewis lung carcinoma (LLC) (Figure 3a high SLK cells (black) were more efficiently transduced by AdHNGR than CD13 low SLK cells (gray). Finally, the role of CD13 was investigated using LLC cells infected with lentiviral vectors expressing either scramble shRNA or shRNA-targeting CD13.…”
Section: Cd13 and Avb3 Integrins Involvement In Ngr-dependent Cell Entrymentioning
confidence: 99%
“…Recently, curcumin was shown to inhibit vascular endothelial cell proliferation in vitro and capillary tube formation in vivo (16)(17)(18)(19). These studies demonstrated that the potent chemopreventive activity of curcumin may, in part, be derived from the direct inhibition of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%